Between Clumsy Hans or Thumbelina? Danish Middle East policy from WWII to the Arab uprisings - Helle Malmvig (Danish Institute for International Studies (DIIS), 2013)
In this paper Helle Malmvig argues that traditionally Denmark has not been very involved in the Middle East. In the 1950s and 1960s, Denmark, much like tiny Thumbelina, adapted to the great-power realities of the day. During the Cold War Denmark was caught in the European Cold War rivalry, and the emphasis was on Denmark's near abroad and its role in multilateral mechanisms and cooperation frameworks such as the UN, NATO and from 1973 the EU. The 1970s and 1980s, however, saw a growing idealism and assertiveness in Danish foreign policy, as well as a new emphasis on areas where Denmark can make a real foreign-policy difference, as evidenced in the large development programmes and the increasing emphasis on human rights and good governance in the 1980s. The 1990s gradually breaks with the ideals of peaceful conflict resolution and the necessity of a UN anchoring. The Danish involvement in, and humanitarian justification for, the missions in the Balkans thus partially paved the way for Denmark's heavy military involvement in the Middle East in the aftermath of the 9-11 terror attacks. Iraq and Libya are thus both legitimized with reference to ideals of democracy and freedom. Over the last decade, Denmark has mainly cooperated with the US and Britain in hotspots such as Afghanistan, Iraq and Libya and will potentially do so in Syria as well. However, Denmark also appears to be a better position to influence the EU's Mediterranean and Middle East policy than ten years ago, due to the knowledge base and ties that have been created throughout the region. It still remains to be seen if the government's intentions to bring the Danish and EU tracks closer together will bear fruit. But Denmark's engagement in the region seems to provide a certain guarantee.
Keywords: 300